TRANSITION PERIODS OF THE PHENOPHASE PROCESSES OF THE INTRODUCED GRAPE CULTIVARS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In the article, the periods of transition of phenological phases of the introduced grape cultivars are studied. Growth phases, budding and branch growth; bloom; the growth of bunches; the ripening of bunches; the periods of shedding of leaves are determined. It was noted that the shortest growing season (117-118 days) of the introduced grape varieties for food was observed in the Chukurak and Husayni Kelin Barmak grape varieties. The longest duration (147-153 days) was observed in the Mirney, Hurmane kyzil, Kara janjal and said gulyami varieties, while the intermediate indicator (124-143 days) was observed in the Ak hussayni, Kadu hussayni and Husayni kelin barmak grape varieties.